Mapping of The Potential Sector of Food and Beverages for Regular Halal Certification and Self Declare in Jember Indonesia - Fathorrazi, Moehammad; Mahardiyanto, Agus; Hardinawati, Lusiana Ulfa (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
At this point, halal certification is a certainty for the mamin. Even though BPJPH as a state institution that focuses on Halal Product Assurance supported by law has started to carry out its activities, the process of halal certification is not without obstacles. Including in the food and beverage sector. This study aims to analyze the potential sectors in food and beverages in Jember Regency that are ready to carry out regular or self-declared halal certification. The population of this research is the superior Mamin MSMEs in Jember which are partially taken as samples. The research data is secondary data obtained from the Jember Regional Office of Industry and Trade, the Cooperative and MSME Office, as well as from the Islamic State University Of Jember. Data collection techniques using questionnaires and in-depth interviews with key informants. This research was conducted using a qualitative phenomenological approach. The results showed that out of a total of 7,336 MSME units in Jember Regency, most were in the Districts of Rambipuji, Kaliwates, Patrang and Jelbuk. With NIB ownership of 7%. In Production (10%), Trade (23%) and Services (01%), as well as other fields. Most of MSMEs (79%) are recorded as not having Halal Supervisors.